2008
DOI: 10.4039/n07-024
|View full text |Cite
|
Sign up to set email alerts
|

The distribution, zoogeography, and composition of Prince Edward Island Carabidae (Coleoptera)

Abstract: Fourteen species of Carabidae are added to Prince Edward Island’s (P.E.I.) faunal list, bringing the known fauna to 167 species. Bembidion nitidum (Kirby) and Bembidion obtusum Audinet-Serville are newly recorded for the Maritime Provinces. Six species are removed from P.E.I.’s faunal list. The history of collecting of Carabidae on P.E.I. is briefly recounted. Despite differences in land area and distance from the mainland between P.E.I., Cape Breton Island, and insular Newfoundland, their carabid faunas exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Th e proportion of Holarctic Carabidae on Prince Edward Island (10.5%) is very similar (Majka et al 2008), however, the proportion of adventive aquatic species in comparison to the overall adventive beetle fauna of Prince Edward Island (21.2%, unpublished data) is very slight.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Th e proportion of Holarctic Carabidae on Prince Edward Island (10.5%) is very similar (Majka et al 2008), however, the proportion of adventive aquatic species in comparison to the overall adventive beetle fauna of Prince Edward Island (21.2%, unpublished data) is very slight.…”
Section: Discussionmentioning
confidence: 93%
“…Th is may represent an island-associated diminution, the paucity of collecting, an area effect, or a combination of all these factors. In comparison, Majka and McCorquodale (2006) found that Prince Edward Island had 39% of the native Maritime Provinces fauna of Coccinellidae, Majka and Jackman (2006) found 40% of Maritime species of Mordellidae, Majka et al (2007) found 32% of the native Maritime Cerambycidae, and Majka et al (2008) found 49% of the native Maritime Carabidae that occur on Prince Edward Island.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEI lies in the Gulf of Saint Lawrence with New Brunswick to its west and south, and Nova Scotia to its east and south. Thus, unsurprisingly and similar to other species groups, the PEI spider fauna largely represents a subset of species found in those adjacent provinces (e.g., Adler et al 2005;Majka et al 2008). Many were likely able to colonize PEI when it was connected to the mainland some 10 000 years ago (Shaw et al 2002).…”
Section: Discussionmentioning
confidence: 92%
“…Many of these publications treated the fauna of the Maritime Provinces or Atlantic Canada as a whole and provided many new records for PE . Fifty-six families were treated in these publications and are listed here in the phylogenetic order used in Bousquet et al (2013) , followed by the number of new records in parentheses for PE : Gyrinidae (5) ( Majka 2008c ), Carabidae (18) ( Majka 2005b , Majka et al 2006a , 2008b ), Haliplidae (1), Dytiscidae (6), Helophoridae (2), Hydrophilidae (12), ( Majka 2008c ), Histeridae (3) ( Majka 2008a ), Ptiliidae (3) ( Majka and Sörensson 2007 ), Leiodidae (2) ( Majka and Langor 2008 ), Silphidae (4) ( Majka 2011g ), Staphylinidae (24) ( Majka 2012b , Klimaszewski and Majka 2007 , 2008a,b, c, 2010), Eucinetidae (1) ( Majka 2010a ), Byrrhidae (4) ( Majka et al 2006b , Majka and Langor 2011b ), Eucnemidae (4) ( Majka 2007c ), Throscidae (2) ( Majka 2011b ), Elateridae (27) ( Majka and Johnson 2008 ), Lampyridae (5) ( Majka 2012a ), Dermestidae (9), Bostrichidae (5), Ptinidae (12) ( Majka 2007b ), Trogossitidae (1) ( Majka 2011c ), Cleridae (7) ( Majka 2006b ), Melyridae (1) ( Majka 2005a ), Erotylidae (2) ( Majka 2007a…”
Section: Introductionmentioning
confidence: 99%